(untitled) (Seminário Internacional de Informação, Tecnologia e Inovação, 2023)
The research aims to analyze how reading is encouraged in early childhood education in schools in the municipal education network of Barra de São Miguel. The methodology is characterized as descriptive with a quali-quantitative approach, the universe is the teachers of the municipal public network of early childhood education. The instrument for data collection was the questionnaire, applied by google forms in July 2023 and the data analysis was done by categories. Research data revealed that teachers carry out projects aimed at children’s reading on a daily basis and 84.2% of teachers encourage students to get to know libraries. It is concluded that teachers from the children’s education network in the municipality of Barra de São Miguel encourage students to read in a creative, participatory and playful way.